Carbon Footprint Reduction Measures for a Higher Educational Institution: Lessons Learned from COVID-19 Pandemic - Jittima Prasara-A; Arika Bridhikitti; Methawee Srinon; Thiwaporn Thuayjan; Areerat Ragsasilp; Thapat Silalertruksa (Chemical Engineering Transactions, 2024)
Carbon Footprint of Organization (CFO) is a vital tool for helping promote higher education institutions towards green university and carbon neutrality. This study assessed the carbon footprint of a faculty at a large university located in north-eastern Thailand. The goal of this study was to estimate carbon footprints from 2015 to 2021 and to see how the COVID-19 pandemic affects carbon footprints in order to find greenhouse gas (GHG) emission reduction measures for the post-COVID-19 period. It was found that, before the pandemic, electricity use was the most significant GHG emissions-contributing activity. During the COVID-19 period, students’ commute reduction causes a substantial decrease in carbon footprint. After the pandemic, the institutions should prioritize measures to reduce electricity consumption, further expand online learning opportunities, encourage telecommuting for staff, and optimize transportation logistics to minimize GHGs.